2021
DOI: 10.1242/jcs.248559
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of lamin A/C determines nuclear stiffness and stress-mediated deformation

Abstract: While diverse cellular components have been identified as mechanotransduction elements, the deformation of the nucleus itself is a critical mechanosensory mechanism, implying that nuclear stiffness is essential in determining responses to intracellular and extracellular stresses. Although the nuclear membrane protein lamin A/C is known to contribute to nuclear stiffness, bulk moduli of nuclei have not been reported for various levels of lamin A/C. Here, we measure the nuclear bulk moduli as a function of lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The nuclear lamina has a well-recognized function of providing mechanical support to the nucleus and acting as a backbone to genome organization [49][50][51][52][53][54][55][56] . Functionally, chromatin contacts with the nuclear lamina have primarily been regarded as a mechanism for gene expression suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear lamina has a well-recognized function of providing mechanical support to the nucleus and acting as a backbone to genome organization [49][50][51][52][53][54][55][56] . Functionally, chromatin contacts with the nuclear lamina have primarily been regarded as a mechanism for gene expression suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Lamins are a group of type V intermediate filaments, which have been a focus of cell stiffness related studies for the past decade. Briefly, the nucleoskeletal protein lamin a/c increases in a scaled manner with matrix/tissue stiffness and contributes to nuclear stiffness and cell stiffness at the perinuclear region ( Swift et al, 2013 ; Srivastava et al, 2021 ). Although a few rudimentary studies have been performed to assess cell stiffness when microtubules are disrupted ( Hobson et al, 2020 ), the role of microtubules in cell stiffness remains relatively unexplored.…”
Section: Determinants Of Endothelial Cortical Stiffnessmentioning
confidence: 99%
“…Nu cle a r la mina de po sitio n is in crea sed in ske le ta l mu scle fib re s fro m tra ined in dividu al s Lamin A localisation and levels regulate nuclear stiffness and nuclear roundness 17,[39][40][41] .…”
Section: R E S U L T Smentioning
confidence: 99%
“…Nuclear lam ina deposition is greater in skeletal m uscle fibres from trained individuals Lamin A localisation and levels regulate nuclear stiffness and nuclear roundness (Lammerding et al, 2006;Swift et al, 2013;Earle et al, 2020;Srivastava et al, 2021). Additionally, it has recently been shown that a Lmna congenital muscular dystrophy alters mechanotransduction in cultured myotubes and attenuates the hypertrophic response to functional overload in mouse skeletal muscle in vivo, implicating a role of Lamin A/C in exercise adaptations (Owens et al, 2021).…”
Section: R E S U L T Smentioning
confidence: 99%